2017
DOI: 10.1371/journal.pone.0177803
|View full text |Cite
|
Sign up to set email alerts
|

Defining the vaccination window for respiratory syncytial virus (RSV) using age-seroprevalence data for children in Kilifi, Kenya

Abstract: BackgroundRespiratory syncytial virus (RSV) is an important cause of lower respiratory tract disease in early life and a target for vaccine prevention. Data on the age-prevalence of RSV specific antibodies will inform on optimizing vaccine delivery.MethodsArchived plasma samples were randomly selected within age strata from 960 children less than 145 months of age admitted to Kilifi County Hospital pediatric wards between 2007 and 2010. Samples were tested for antibodies to RSV using crude virus IgG ELISA. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 30 publications
4
31
1
Order By: Relevance
“…Though RSV disease burden is seen in infants less than 5 months age, in view of the possibility of interference of maternal antibodies with the vaccine‐induced immune response, 6 months seems to be the appropriate age for vaccination, whenever available. In Kenya, 25% of subjects at ~6 months age were antibody positive increasing to 43% at 9 months and 100% from 3 years onwards; birth status was not considered . RSV vaccine immunization at greater than 5 months was suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though RSV disease burden is seen in infants less than 5 months age, in view of the possibility of interference of maternal antibodies with the vaccine‐induced immune response, 6 months seems to be the appropriate age for vaccination, whenever available. In Kenya, 25% of subjects at ~6 months age were antibody positive increasing to 43% at 9 months and 100% from 3 years onwards; birth status was not considered . RSV vaccine immunization at greater than 5 months was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using catalytic models have determined appropriate age for vaccination. On the basis of the samples collected from Kenya (2007‐2010) and Brazil (1996), the vaccination windows were suggested to be 4.7 to 15.1 and 3.3 to 19.1 months respectively. Clearly, epidemiology of RSV directs immunization strategies for individual countries.…”
Section: Discussionmentioning
confidence: 99%
“…RSV-associated infection is known to be very common as shown with ad hoc age-stratified serological studies, for example a study in Kenya indicated that 100% of the population are likely to be infected by 3 years of age. 3 Only a proportion of these infections, however, will be symptomatic and a smaller proportion of them will present to health services. In a prospective cohort study in Finland, the average annual symptomatic RSV infection rate was 275/1000 in children <3 years of age over two RSV seasons, of whom 58% developed acute otitis media, and only 3% of those symptomatic were hospitalized.…”
Section: Burden Of D Is E a S E Due To R S Vmentioning
confidence: 99%
“…12,59,67 Most of the RSV neutralizing activity is undetectable in infants who are 4-6 month of age. 66,67 The mechanism by which the level of antibodies (neutralizing or not) influences repression of RSV immunity is still not clear.…”
Section: Inhibitory Effect Of Pre-existing Maternal Antibodiesmentioning
confidence: 99%